(untitled) (Research, Society and Development, 2023)
Chronic kidney disease (CKD) is a public health problem that has been highlighted in recent years. It is a disease caused by the destruction of the renal functional unit, called the nephron, and which has different stages until it leads to total kidney failure. This work aims to elucidate the particularities related to dental care for people with chronic kidney disease, on hemodialysis and kidney transplant recipients, in addition to elucidating protocols on care in caring for these patients in the routine of the dental office. To carry out this narrative review, the Scielo and Pubmed databases were used, with the following keywords: “chronic renal failure” “dentistry” and “oral manifestations” associated by the Boolean operator “E”, as well as their English counterparts . Articles were selected without limiting the year of publication on the topic, including articles published in English and Portuguese available in full. A qualitative assessment of the published content was carried out. In this study, the consequences of compromised kidney function and how it can directly impact the lives of sufferers were addressed. The fact that systems of the human body are compromised due to this disease makes it necessary for the dental surgeon to have training and knowledge applied in his routine care for these patients. It is worth noting that CKD can directly or indirectly affect the oral health of patients with it. This review also indicated some of the medications of choice for these patients in Dentistry and what dental care protocols should be like, taking into account the different stages in which the disease may be found and whether this patient is transplanted or not.